Anti-invasion activities of heat-killed lactic acid bacteria isolates against Salmonella enterica serovar Typhimurium - Anis Syahirah Saifor Adzuan; Sharifah Aminah Syed Mohamad; Rashidah Iberahim; Noor Nadia Syahira Mohd Kamal; Nurliana Abd Mutalib; Nur Intan Hasbullah; Muneer Alsaydi; Nor'aishah Hasan; Low Kheng Oon; Olaide Olawunmi Ajibola; Rozila Alias; Maimunah Mustakim; et al. (Iranian Journal of Microbiology)
Background and Objectives: The most common cause of severe foodborne salmonellosis is S. Typhimurium. Its interaction with intestinal epithelial cells is little known. Lactic acid bacteria (LAB) were recognized as a prominent probiotic gastrointestinal microbiota of humans and animals that confer health-promoting and protective effects. This study aims to determine the anti-invasion and antibacterial effects of heat-killed LAB (HK-LAB) isolates against S. Typhimurium towards human intestinal cells. Materials and Methods: 12 HK-LAB isolates from 3 sources of origin (stingless bee, plant, and food) were tested to determine the adhesion of HK-LAB to Caco-2 cells, anti-invasion and antibacterial activities against S. Typhimurium, the adhesion and invasion pattern of S. Typhimurium on intestinal epithelial cells (Caco-2) and assessing the effect of LAB on the S. Typhimurium-host cell interaction. Results: Tairu isolates from food have the highest adhesion rate with 19 ± 1.32/10 Caco-2 cells followed by HK-LAB R-isolate from plant 17 ± 0.70/10 Caco-2 cells, which is similar to the control (Lactobacillus casei). In the anti-invasion assay, the two HK-LAB isolates that had the strongest adherence to Caco-2 cells, Tairu-isolate inhibited at 78.1 ± 3.06% and R-isolate inhibited at 64.76 ± 9.02% compared to the positive control (63.81 ± 1.15%), which led to increased suppression of S. Typhimurium accordingly. Tairu and R isolates were tested for their antibacterial ability against S. Typhimurium. Both R and Tairu isolates displayed strong inhibition zones (27 ± 0.06 mm, 23 ± 0.06 mm) respectively. Conclusion: These findings suggest that the anti-invasion activities of HK-LAB R and Tairu may correlate to their bactericidal effects that serve to protect the host from infection.